Non-accounting Aspects of IFRS Implementation in the USA - Roe, Jana; Mejzlík, Ladislav, 1961-; Zárybnická Žárová, Marcela, 1959-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
In the last 20 years, IASB IFRS has been promoted as the IFRS has been adopted by many major economies as for financial reporting and is poised to become even more widely accepted and used in the near future, with the main objective of unifying world financial reporting by making statements more comparable. The second key player in the field of financial reporting is US GAAP, used by American publicly traded companies, accounting roughly for approximately one-third of the world's capitalization. Although many countries, in concluding members of the EU, have accepted IFRS without significant changes to their existing financial reporting standards or their infrastructure, SEC in the USA has lead a long process of convergence with IFRS from the technical side and also the regulators and general environment has been preparing for the change, with the aim of ensuring smooth and successful transition, resulting in a higher quality of IFRS adoption. The main problem, which leads to the research presented in this dissertation is whether to approach international accounting harmonization from the top-down or bottom-up. The main objective of the dissertation is was to contribute to the analysis of the significance of the impact of non-accounting (environmental) factors on financial reporting quality, specifically the adoption of IFRS. The dissertation accomplishes the main goal by utilizing the survey method of analysis to accumulate research to date, analyze available evaluation methods and to describe the control environment, USA. The second stage of the analysis involves constructing a comprehensive evaluation model, which enables a comprehensive analysis of the relationship between environment and financial reporting. The model developed in the dissertation is intended for use by researchers for a comprehensive, inter-disciplinary, empirical study of the environmental effects on financial reporting.
Vedoucí práce: Ladislav Mejzlík
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor disert. práce]; disertace; dissertations